A concepção e o lugar que a eudaimonia ocupa na ética Nicomaqueia de Aristóteles - Lopes, Vera Lucia (2017)
The Aristotelian ethics is articulated from the research on which is the supreme good of man and the purpose for which all things tend. Artistotle says that happiness (eudaimonia) is this good that we all seek in life and, therefore, is the end to which all things desired by man tend. For Aristotle, eudaimonia is the successful accomplishment of the human being viewed as a rational political animal. Thus, the man is happy when performing the purpose for which he exists, i.e., when performing the work (érgon) of its own. This study, which focuses on the part of the Nicomachean Ethics that became known as “The treaty of virtue” (Books I-IV), aims at understanding the design and place that occupies eudaimonia in the ethics of Aristotle. Therefore, we investigate some concepts of Aristotelian ethics closely linked with his conception of eudaimonia. In conclusion to the paper, we present a recent debate that has become paradigmatic in studies of Aristotelian ethics. This is the debate between the positions of two great contemporary Aristotelians, Hardie and Ackrill on the conception of eudaimonia as a supreme good, to be understood as an inclusive one (Hardie) or a dominant one of all the others (Ackrill)